2021
DOI: 10.3390/cells10051078
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lipids, Lipid Metabolism and Ectopic Lipid Accumulation in Axon Growth, Regeneration and Repair after CNS Injury and Disease

Abstract: Axons in the adult mammalian nervous system can extend over formidable distances, up to one meter or more in humans. During development, axonal and dendritic growth requires continuous addition of new membrane. Of the three major kinds of membrane lipids, phospholipids are the most abundant in all cell membranes, including neurons. Not only immature axons, but also severed axons in the adult require large amounts of lipids for axon regeneration to occur. Lipids also serve as energy storage, signaling molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 254 publications
(318 reference statements)
0
18
0
Order By: Relevance
“…S1) (Leach et al ., 2021; Lu et al ., 2022) based on predicted functions (e.g. cell-cell contact, lipid metabolism, immune responses) that are critical during tissue regeneration in a variety of organs/systems (Roy and Tedeschi, 2021; George et al ., 2021). To generate knockouts, we modified an existing CRISPR/Cas9-based F0 mutagenesis methodology (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1) (Leach et al ., 2021; Lu et al ., 2022) based on predicted functions (e.g. cell-cell contact, lipid metabolism, immune responses) that are critical during tissue regeneration in a variety of organs/systems (Roy and Tedeschi, 2021; George et al ., 2021). To generate knockouts, we modified an existing CRISPR/Cas9-based F0 mutagenesis methodology (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the regulation of cytoskeleton and metabolic signaling pathways were involved in tissue regeneration for the cell movement, growth, and proliferation [ 33 , 34 ]. Studies showed that the modification of lipid metabolism is needed in liver and axon regeneration [ 35 , 36 ]. Lastly, the assembly and activity of ribosomal proteins are required for protein synthesis and involved in regeneration process [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The same method can be adapted to measure lipolytic potential of brown adipose tissue. Although this technique can reliably detect endogenous lipolytic potential of adipose tissue as a functional readout of metabolic homeostasis in health and disease ( Roy and Tedeschi, 2021 ), it remains an end point assessment. When continuous assessment is necessary, in-situ microdialysis of adipose tissue should be considered as it enables real-time detection of lipolysis in response to an external stimuli like cold exposure ( Arner et al., 1988 ; Weir et al., 2018 ).…”
Section: Limitationsmentioning
confidence: 99%